PENGARUH BUAH DAN SAYUR TERHADAP PENINGKATAN KUALITAS TIDUR PADA LANSIA : Systematic Review - Hasna Iffah Dias Labibah (2021)
As the population of elderly escalates each year, various health problems also coexist due to the aging process that occurs among elderly such as decreased sleep quality. The prolonged and insurmountable decline in sleep quality can decrease the quality of life and lead to an increase in mortality rates among elderly. Thus, an effective and safe for long-term use therapy is needed to overcome this, such as fruits and vegetables consumption. Objective: Knowing the effect of fruits and vegetables on improving sleep quality among elderly. Methods: This study used a Systematic Review design. A literature search was conducted through several databases such as PubMed, EBSCO, Cochrane and through handsearching. The identified articles were selected using eligibility criteria then reselected gradually using PRISMA-P method to be further analyzed qualitatively. Results: 5 relevant literatures were obtained. 4 literatures showed an influence of fruits and vegetables consumption on improving sleep quality in the elderly while 1 literature showed an influence on sleep quality only on vegetables consumption and women gender only. The improvement in sleep quality was assessed from improved sleep duration, improved sleep efficiency, decreased sleep latency, decreased sleep disorders and improved overall sleep quality. Conclusion: Fruits and vegetables consumption has an influence on improving sleep quality among elderly.